STUDI KASUS IMPLEMENTASI EVIDENCE-BASED NURSING: WATER TEPID SPONGE BATH UNTUK MENURUNKAN DEMAM PASIEN TIFOID - Andan Firmansyah; Henri Setiawan; Heri Ariyanto (Viva Medika, 2021)
Typhoid is an acute febrile illness caused by a bacterial infection of salmonella typhi and its endotoxin stimulates the synthesis and release of pyrogens by leukocytes in inflamed tissue resulting in hyperthermia. A non-pharmacological technique that can be used to reduce the increase in body temperature in hyperthermic patients is by doing a water tepid sponge bath, this technique is still rarely found in the field. Nurses tend to give antipyretics more often when children experience hyperthermia. This case study aims to present the results of implementing the evidence-based nursing water tepid sponge bath as an effort to reduce fever in typoid patients. Physical examination was performed using the head to toe method in typoid patients. The North American Nursing Diagnosis Association (NANDA) is used to determine nursing diagnoses. Meanwhile, nursing intervention refers to the Nursing Intervention Classification (NIC) and the Nursing Outcomes Classification (NOC). A hyperthermic nursing diagnosis with a diagnosis number 00007 is given a nursing intervention in the form of a water tepid sponge bath. After being given nursing intervention for 7 days, hyperthermia was resolved by the criteria that the patient's body temperature returned to normal 36.2 °C. Water tepid sponge bath is effective in reducing body temperature in typoid patients